P216 Impact of Tachycardia and New Onset Atrial Fibrillation in Acute Exacerbations of COPD. (19th November 2012) - Short, PM; Chalmers, JD; Akram, AR; Singanayagam, A; Schembri, S; Williamson, PA
Abstract : Introduction and Objectives: Cardiac arrhythmias are regularly found in patients with COPD, with higher frequencies reported during exacerbations. We wished to examine the impact of tachycardia and new onset atrial fibrillation (AF) on long term outcome in patients hospitalised with a COPD exacerbation. Methods: A prospective observational cohort study of patients admitted with an acute exacerbation of COPD (AECOPD) was performed. Patients were >40 years of age, with spirometry confirmed COPD, admitted to one of 12 UK centres between 2009–2012. Hazard ratios for mortality and cardiovascular events at 1 year follow up, based upon the presence of either sinus tachycardia or new onset AF at the initial hospital admission were calculated through Cox proportional hazard regression analysis following correction for influential covariates. Logistic regression was performed to calculate odds ratios (OR) identifying predictor variables of both sinus tachycardia and AF. Results: 1343 patients were included in our study. New onset AF was recorded in 155 patients (12%) of patients. Mean (IQR) age was 72(63–79). Mean (95%CI) FEV1% predicted and MRC dyspnoea score were 46 (34–67) and 4 (3–5) respectively. Hazard Ratios (95%CI) for new onset AF and tachycardia are displayed in table 1 . Factors predicting new onset AF included; history of IHD (OR 4.8; 95%CI 2.95–7.80), increasing age (OR 1.03; 95% CI 1.01–1.07) and worsening MRC dyspnoea score (OR 1.74; 95%CI 1.31–2.29). Prior beta blocker use was not significant (OR 0.68; 95%CI 0.35–1.28). For sinus tachycardia >120bpm, there were significant relationships for MRC dyspnoea score (OR 1.73; 95%CI 1.43–2.09), respiratory acidosis (OR 1.80; 95%CI 1.20–2.70) and aminophylline treatment (OR 1.53; 95%CI1.06–2.20). Prior beta blocker use was protective (OR 0.68; 95% CI 0.47–0.97). Conclusions: The presence of tachycardia and new onset AF in patients admitted with AECOPD are associated with a deleterious effect on short and long term mortality. For sinus tachycardia risk was greatest around the time of exacerbation, however new onset AF also heralds more significant 1 year mortality and risk of cardiac events.